1982
DOI: 10.1007/bf00496668
|View full text |Cite
|
Sign up to set email alerts
|

Morphological studies on the epiphyseal growth plate combined with biochemical and X-ray microprobe analyses

Abstract: The epiphyseal growth plate of the domestic pig was investigated topologically combining biochemical methods with electron microprobe microanalyses both correlated to histological controls. A lateral resolution of about 50 micrometer was reached. Highest nuclease activity was found in the lower columnar cell zone, while alkaline phosphatase showed maximal activity in the hypertrophic area, connected with maximal values for extractable, organically bound phosphorus, and extractable Ca and Mg. Acid phosphatase a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
1

Year Published

1988
1988
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(54 citation statements)
references
References 14 publications
3
50
1
Order By: Relevance
“…Alkaline phosphatase activity increased markedly between day 12 and 15 of culture, which correspond in this culture model to hypertrophy of chondrocytes and with the onset of mineralization [15]. Furthermore, similar alkaline phosphatase kinetic expression has been reported in vivo in the epiphyseal growth plate using immunohistochemical and biochemical analyses [42,43]. Additionally, studies using bone-forming cells have also showed an increase of alkaline phosphatase in the presence of bioactive glasses [3,4].…”
Section: Article In Pressmentioning
confidence: 65%
“…Alkaline phosphatase activity increased markedly between day 12 and 15 of culture, which correspond in this culture model to hypertrophy of chondrocytes and with the onset of mineralization [15]. Furthermore, similar alkaline phosphatase kinetic expression has been reported in vivo in the epiphyseal growth plate using immunohistochemical and biochemical analyses [42,43]. Additionally, studies using bone-forming cells have also showed an increase of alkaline phosphatase in the presence of bioactive glasses [3,4].…”
Section: Article In Pressmentioning
confidence: 65%
“…Magnesium is closely associated with mineralization of calcified tissues [4] and indirectly influences mineral metabolism [8]. Its role, however, has not been fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Mg is also undoubtedly one of the most important elements in the human body. It is closely associated with mineralization of calcined tissues [10] and indirectly influences mineral metabolism [11]. Furthermore, diopside (CaMgSi 2 O 6 ), a Ca, Si and Mg-containing ceramic, has been reported to possess apatite-formation ability in SBF and can closely bond to bone tissue when implanted in rabbits [6][7][8].…”
Section: Introductionmentioning
confidence: 99%